Business Model and Islamic Boarding School Business Development Strategy (Case Study Islamic Boarding School Sido Giri Pasuruan, East Java) - Zaki, I; Mawardi, I; Widiastuti, T; Hendratmi, A; Budiantoro, R A (KnE Social Sciences, 2019)
Islamic Boarding School is Islamic school that most of students are boarders. In the last 20 years, when the Islamic economy developed in Indonesia, many islamic boarding school established financial institutions and businesses that comply to Islamic law. The existence of the business and financial institutions (business network) were expected to encourage the implementation of Islamic law on economics and business in society, and also able to carry out economic and business practices according to sharia. This study will examine the existence of business network model and what are the benefits of business network model for the While in the era of colonialism adjustment occurs through the transformation of values where the islamic boarding school acts as an Islamic institution or institutionalization of Islamic values that have a mission-oriented ideology-political or religious-political. Where the motivation is to seize independence and liberate the people from the shackles of penghisaban by the invaders (Arifin, 2013). For now the existence of islamic boarding school is more related to learning process and education. In other words, islamic boarding school is a religious education institution capable of issuing certificates recognized in the national education system in Indonesia. This can be regarded as a islamic boarding school negotiation of new values that develop in society as a result of the advancement of science, knowledge, and technology (Izfannah, 2012).sustainability of business unit. The renewal of this research illustrates the business model practiced by islamic boarding school cottages especially PP Sidogiri as a whole and formulates the right business development strategy for business unit PP Sidogiri in order to maximize the role and social function of the islamic boarding school business unit. This research uses case study method on mixed islamic boarding school especially on Sidogiri Islamic Boarding School. The results of research to find out the ideal strategy in the implementation of business network as the development of a business model strategy of Islamic boarding schools in order to develop Islamic boarding school’s business. Keywords: Business Model, Strategy, Islamic Boarding School